Effects of mothers' postpartum support needs and the level of support they received on breastfeeding self-efficacy (Annals of Medical Research, 2022)
Aim: This descriptive and correlational study was conducted to examine the effects of postpartum support needs of mothers and the support they received on breastfeeding self-efficacy.Materials and Methods: The study was conducted in 431 mothers with 4-8 weeks old babies, who presented to Karaman city-center family health units between November 2019 and June 2020. For data collection, a personal information form, the Postnatal Support Scale (PSS), and the Breastfeeding Self-Efficacy Scale-Short Form (BSES) were used. In independent groups, t-test, one-way analysis of variance, Pearson correlation analysis, and multiple regression analysis were used.Results: The mean BSES score of the mothers included in the research was 57.53±11.36, the mean PSS Importance of Needs subdimension score was 168.48±20.32, and the mean PSS Support Received subscale score was 162.25±31.25. In the study, it was found that the BSES score was affected by the PSS Support Received subdimension score (p
Keywords: Postpartum period; Support; Breastfeeding